Do extracellular vesicles have specific target cells?; Extracellular vesicle mediated embryo maternal communication - Dissanayake, Keerthie; Godakumara, Kasun; Muhandiram, Subhashini; Kodithuwakku, Suranga; Fazeli, Alireza (Frontiers in Molecular Biosciences, 2024)
Extracellular vesicles (EVs) serve as messengers for intercellular communication, yet the precise mechanisms by which recipient cells interpret EV messages remain incompletely understood. In this study, we explored how the origin of EVs, their protein cargo, and the recipient cell type influence the cellular response to EVs within an embryo implantation model. We treated two types of EVs to 6 different recipient cell types and expression of zinc finger protein 81 (ZNF81) gene expression in the recipient cells were quantified using quantitative polymerase chain reaction (qPCR). The results showed that downregulation of the ZNF81 gene is a specific cellular response of receptive endometrial epithelial cells to trophoblast derived EVs. Protein cargo analysis revealed that the proteomic profile of EVs depends on their cell of origin and therefore may affect the recipient cell response to EVs. Furthermore, trophoblastic EVs were found to be specifically enriched with transcription factors such as CTNNB1 (catenin beta-1), HDAC2 (histone deacetylase 2), and NOTCH1 (neurogenic locus notch homolog protein 1), which are known regulators of ZNF81 gene expression. This enrichment suggests a potential association between these transcription factors and the specific functionality of trophoblastic EVs. The current study provided compelling evidence supporting the existence of EV specificity, where the characteristics of both the EVs and the recipient cell type collectively contribute to regulating EV target specificity. This in vitro embryo implantation model and ZNF81 read-out provides a unique platform to study EV specific functionality in natural cell-cell communication.